The magic mirror: a novel intraoperative monitoring method for parathyroid glands - Yuan, Yue; Li, Xiao; Bao, Xin; Huangfu, Mingmei; Zhang, Hong (Frontiers in Endocrinology, 2023)
The accurate detection of parathyroid glands (PGs) during surgery is of great significance in thyroidectomy and parathyroidectomy, which protects the function of normal PGs to prevent postoperative hypoparathyroidism and the thorough removal of parathyroid lesions. Existing conventional imaging techniques have certain limitations in the real-time exploration of PGs. In recent years, a new, real-time, and non-invasive imaging system known as the near-infrared autofluorescence (NIRAF) imaging system has been developed to detect PGs. Several studies have confirmed that this system has a high parathyroid recognition rate and can reduce the occurrence of transient hypoparathyroidism after surgery. The NIRAF imaging system, like a magic mirror, can monitor the PGs during surgery in real time, thus providing great support for surgeries. In addition, the NIRAF imaging system can evaluate the blood supply of PGs by utilizing indocyanine green (ICG) to guide surgical strategies. The NIRAF imaging system and ICG complement each other to protect normal parathyroid function and reduce postoperative complications. This article reviews the effectiveness of the NIRAF imaging system in thyroidectomies and parathyroidectomies and briefly discusses some existing problems and prospects for the future.